Living heritage under threat: Structural determinants of traditional game decline and preservation in the Tribal Districts of Maharashtra, India - Ashish Govindrao Barde; Assia Aboubakar Mahamat (Journal of Sports and Physical Activity, 2026)
Background: Traditional games among Maharashtra's tribal communities represent an important form of intangible cultural heritage, preserving embodied knowledge, social values, and collective memory. However, youth participation has declined dramatically from approximately 67% in the early 1990s to 18.3% today, posing a serious threat to the continuity and preservation of this cultural heritage. Aim: To investigate the factors influencing youth participation in traditional tribal games in Maharashtra and to explore the challenges and opportunities related to the transmission and preservation of this intangible cultural heritage. Methods: A sequential explanatory mixed-methods design was employed. Quantitative data were collected through surveys involving 480 respondents from six tribal-majority districts in Maharashtra (Nashik, Nandurbar, Amravati, Gadchiroli, Thane, and Palghar). Qualitative data were gathered through 36 in-depth interviews and six focus group discussions. Multiple regression analysis was used to identify predictors of youth participation, while thematic analysis was conducted to explore underlying themes. Results: Multiple regression analysis revealed that school curriculum integration (β = .381), community festival frequency (β = .298), and digital technology use (β = −.241) were significant predictors of youth participation (R² = .465, p < .001). Qualitative analysis identified five key themes: structural displacement, institutional marginalization, a gendered knowledge crisis, community resilience factors, and conditional youth receptivity. The findings also showed that older women possess the highest levels of traditional game knowledge but face challenges in transmitting it due to disrupted female-specific transmission pathways resulting from urban migration. Conclusion: The study suggests that traditional game preservation should move beyond UNESCO's documentation-focused framework toward an approach that emphasizes community agency and living heritage ecosystems. To support sustainable preservation, the study recommends integrating traditional games into school curricula, revising eligibility criteria for heritage programs, and implementing gender-inclusive preservation strategies.